Analysis of the Rationality of Antibiotic Use in Pediatric Bronchopneumonia Patients and its Impact on Clinical Outcomes and Costs at RS Columbia Asia Pulomas Jakarta Period April 2024–April 2025 - Wahyu Agung Yuwono; Sondang Khairani; Assajadda Lizikri; Ni Made Dwi Sandhiutami (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Bronchopneumonia is one of the leading causes of morbidity and mortality in the pediatric population, especially in developing countries such as Indonesia. This condition also imposes a considerable economic burden due to the long duration of treatment and the frequent use of antibiotics, which are often inappropriate. This study aimed to evaluate the rationality of antibiotic administration in pediatric patients hospitalized with a diagnosis of bronchopneumonia at Columbia Asia Pulomas Hospital Jakarta during the period from April 2024 to April 2025, and to analyze its effect on clinical outcomes and treatment costs. This study used a retrospective cross-sectional design with a total sampling approach of 164 patients through a review of medical records and cost data. The rationality of antibiotic therapy was assessed using the Gyssens method, and the relationship between variables was analyzed using bivariate statistical tests. The study found that 71.9% of rational antibiotic use correlated with a higher clinical improvement rate of 80.5% compared to 52.2% for irrational antibiotic use (p = 0.000). However, there was no significant difference in the duration of hospitalization between rational antibiotic use (4.70 ± 0.82 days) and irrational antibiotic use (5.41 ± 2.25 days) (p = 0.612), nor in the total cost of hospitalization (rational use: Rp 15,956,032.66 ± Rp 5,568,892.10 vs. irrational use: Rp 18,801,283.94 ± Rp 11,292,810.87) (p = 0.658). These results emphasize the importance of antibiotic rationality analysis as an effort to improve clinical outcomes without having a significant impact on cost efficiency or treatment duration.